OXIDATIVE STRESS AND POSSIBILITY TO CORRECT IT WITH ANGIOTENSIN CONVERTING ENZYME INHIBITORS IN PATIENTS WITH MYOCARDIAL INFARCTION ASSOCIATED WITH DIABETES MELLITUS TYPE 2 - K. S. Lexina; N. Y. Timofeeva; V. S. Zadionchenko; G. G. Shehian; K. A. Aldushina (Столичная издательская компания, 2015)
The review is devoted to the modern data about mechanisms of cardiovascular dysfunction in patients suffering diabetes mellitus type 2, especially to the role of oxidative stress. It is determined that oxidative stress is involved in the development of myocardial ischemia, reperfusion-syndrome, endothelial dysfunction and atherogenesis. There are data that angiotensin converting enzyme inhibitor, zofenopril, has both cardio- and vasoprotective activities as well as antioxidative effect. These features are rationales to use it in patients with ischemic heart disease and diabetes mellitus.